Sistem Management Absensi Di SMP Islam Bahrul Ulum - Ade Surya Dinata; Arief Rahman Dwi Putra; Jalu Somala; Hariko Saputra; Agung Wijoyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The impact of the Covid-19 pandemic in the world of education has made many changes, from the learning system to the attendance system. Management Information Systems are essential in the world of education. It aims to support management functions and activities in an educational organization, including Bahrul Ulum Islamic Junior High School. This junior high school is on Jalan. Kali Baru RT03/RW06, Kelurahan. New Parigi, District. Pondok Aren, South Tangerang City. Teacher attendance at Bahrul Ulum Islamic Junior High School has used a web-based system, where this system will make it easier for teachers to take attendance using their respective cellphones or laptops. This application is a web-based system that scans the barcode in the teacher's room. Thus, teachers do not need to write initials manually anymore and will be saved immediately, so there is no need for many documents to be stored, because they will be directly stored on the administrator's computer.